DESEMPENHO AGRONÔMICO DE LINHAGENS AVANÇADAS DE AMENDOIM NA REGIÃO CONE-SUL DE MATO GROSSO DO SUL - Henrique de Oliveira Gaiola , Lucas; Rafael Simbre Barbosa , Bruno; Abel dos Santos , Benjamin; Alves Gottardi, Guilherme; Alves Gottardi, Gabriel; Zoz , Tiago (ANAIS DO ENIC, 2026)
-